(untitled) (Samriddhi Journal of Development Studies, 2025)
This study examines the intricate relationship between cultural identities, Migration, and heritage in the historic City of Dolakha, Nepal. Through a comprehensive analysis of the socio-cultural transformations in the region, the study highlights how migration patterns—both voluntary and forced — have shaped the local population’s cultural landscape. It examines the preservation and adaptation of heritage practices in the face of changing demographics and the impact of globalization on local traditions. Using qualitative and quantitative methodologies, including short surveys, various types of interviews, and ethnographic observations, the data are analyzed using different methods, including content, thematic, and comparative analysis. The research provides insights into the experiences of migrants and their contributions to the evolving identity of Dolakha. The findings highlight the resilience of cultural heritage in the face of challenges and emphasize the importance of fostering an inclusive narrative that acknowledges the diverse identities within the community. This introduction sets the stage for a deeper understanding of the dynamics of culture, identity, and heritage in a rapidly changing world.